64‐1: Local Dimming Technology of Scene‐Adaptation for Massive Mini‐LED. Issue 1 (28th June 2022) - Ma, Xitong; Zhang, Shuguo; Duan, Ran; Wu, Congrui; Wang, Xian; Geng, Lihua; Li, Tao
Abstract : Mini‐LED Backlight Units can reduce the light mixing distance and the number of backlight blocks, making the monitors lighter and thinner, achieving higher contrast and better effects. As a leading company in the panel display industry, BOE has been developing Mini‐LED technology since 2016, and has developed 65', 75', and 86' smart commercial display monitors based on Mini‐LED technology.This paper verifies the Local Dimming technology with multiple partitions using FPGA, it's safe to say that it obtains a finer light distribution and less halo effect, which will strongly support MiniLED display products in the future.